Biopolymer-Based Adsorption of Congo Red Using Modified Κ-Carrageenan: Towards Safer Water and Environmental Health Protection - Wan Farahiyah Wan Kamarudin; Asmadi Ali; Sofiah Hamzah; Northaqifah Hasna Mohamed Khir; Abd Rahman Mat Amin (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: The discharge of synthetic dyes such as Congo Red (CR) into water systems poses serious threats to aquatic biodiversity, deteriorates water quality, and raises public health risks due to their toxicity, persistence, and tendency to bioaccumulate. This study investigates the potential of chemically modified κ-carrageenan as a biosorbent for CR removal under varying conditions. Methods: Two forms of κ-carrageenan were prepared: unmodified (κC) and modified (mκC). Functional groups were identified using Fourier Transform Infrared Spectroscopy (FTIR), while surface morphology was examined via Scanning Electron Microscopy (SEM). Batch adsorption experiments were conducted to assess how dye concentration, contact time, and adsorbent amount affect Congo Red removal, measured by UV-Vis spectrophotometry and analyzed using Langmuir and Temkin isotherm models. Results and Discussion: The mκC achieved 93.3% removal efficiency at an initial CR concentration of 20 mg/L, reaching equilibrium within 60 minutes at an optimal dosage of 0.3 g. FTIR confirmed the presence of functional groups such as carbonyl, sulfonate, and amide. SEM revealed an increase in the biosorbent's roughness and porosity. Isotherm modelling showed a strong fit to the Langmuir model, with an R² value of 0.9974 and a maximum adsorption capacity of 476.19 mg/g. The Temkin model also revealed a good correlation (R²=0.9511), indicating that chemisorption is the primary mechanism of adsorption. Conclusion: Modified κ-carrageenan is a cost-effective and biodegradable biosorbent for dye removal, with potential for wastewater treatment. Future research on regeneration and real-world applications will enhance its role in improving water quality and protecting environmental health.